Linear spaces: history and theory - Albrecht Beutelspracher (Le Matematiche, 1990)
Linear spaces belong to the most fundamental geometric and combinatorial structures. In this paper I would like to give an onerview about the theory of embedding finite linear spaces in finite projective planes.